Lithium ion battery and preparation method thereof

By optimizing the parameters of the positive electrode active material, negative electrode active material and electrolyte in lithium-ion batteries, the problem of high polarization of lithium-ion batteries is solved, and the high-rate load performance of the battery is significantly improved.

CN119786703AInactive Publication Date: 2025-04-08EVE ENERGY CO LTD

Patent Information

Application Number
CN202412000209.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have a high degree of polarization, which affects the battery's discharge ability under high-risk loads.

Method used

By optimizing the particle size of the positive electrode active material and the negative electrode active material, the conductivity of the electrolyte, and the surface density and thickness of the electrode layer, a synergistic effect is formed to reduce the polarization of the battery.

Benefits of technology

It significantly reduces the polarization of lithium-ion batteries and improves the battery's voltage holding capability and charge and discharge performance under high-rate loads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227539670000071
    Figure BDA0005227539670000071
  • Figure BDA0005227539670000081
    Figure BDA0005227539670000081
Patent Text Reader

Abstract

The invention provides a lithium ion battery and a preparation method thereof. The lithium ion battery comprises a positive plate, an electrolyte and a negative plate, the positive plate comprises a positive active layer, the positive active layer contains a positive active material, and the D50 particle size of the positive active material is 4-10 [mu] m; the negative plate comprises a negative active layer, the negative active layer contains a negative active material, and the D50 particle size of the negative active material is 10-20 [mu] m; and the conductivity of the electrolyte solution is 10.0 to 12.0 mS / cm. As a whole, the lithium ion battery is improved by a single factor, so that the influence on polarization reduction is limited. The particle size of the positive electrode active material, the particle size of the negative electrode active material and the conductivity of the electrolyte are synchronously improved at the same time, and through the synergistic effect of the three materials, the polarization of the lithium ion battery can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery and a method for preparing the same. Background Art

[0002] The polarization size of lithium-ion batteries can be used as a way to evaluate the performance of batteries. The existence of polarization seriously affects the discharge capacity of batteries under high-rate loads. Under high-rate discharge conditions, the smaller the battery polarization, the higher the initial value of the voltage will be, thereby releasing more capacity. In order to meet the demand for higher power use, more and more scholars have invested in the research of reducing the polarization of lithium-ion batteries. However, the effect of existing research on reducing the polarization phenomenon in batteries still needs to be improved. Summary of the invention

[0003] The main purpose of the present application is to provide a lithium ion battery and a preparation method thereof, so as to solve the problem of high polarization degree of lithium ion batteries in the prior art.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises a positive electrode active material, and the D50 particle size of the positive electrode active material is 4 to 10 μm; the negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises a negative electrode active material, and the D50 particle size of the negative electrode active material is 10 to 20 μm; and the conductivity of the electrolyte is 10.0 to 12.0 mS / cm.

[0005] Furthermore, the ratio of the D50 particle size of the positive electrode active material to the D50 particle size of the negative electrode active material is 1:(2-2.5).

[0006] Furthermore, the surface density of the positive electrode active layer is 100 to 140 g / m 2 ; and / or, the surface density of the negative electrode active layer is 50 to 100 g / m 2 .

[0007] Furthermore, the thickness of the positive electrode active layer is 70 to 100 μm; and / or the thickness of the negative electrode active layer is 70 to 100 μm.

[0008] Furthermore, the positive electrode active layer further contains a conductive agent and a first binder; further, the mass ratio of the positive electrode active material, the conductive agent and the first binder is 100:(1-3):(1-3).

[0009] Further, the above-mentioned positive electrode active material is selected from any one or more of lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate; and / or, the conductive agent is selected from any one or more of carbon nanotubes, graphene and conductive carbon black; and / or, the first binder is selected from any one or more of polytetrafluoroethylene, carboxylated polyvinylidene fluoride and polyimide; further, the positive electrode active material is lithium cobalt oxide; and / or, the conductive agent is carbon nanotubes; and / or, the first binder is polytetrafluoroethylene.

[0010] Furthermore, the negative electrode active layer further contains a second binder and a thickener; further, the mass ratio of the negative electrode active material, the second binder and the thickener is 100:(1-5):(1-5).

[0011] Furthermore, the negative electrode active material is graphite; and / or the second binder is styrene-butadiene latex binder; and / or the thickener is sodium carboxymethyl cellulose.

[0012] According to another aspect of the present application, a method for preparing the aforementioned lithium-ion battery is provided, and the method comprises: step S1, mixing a positive electrode active material, a conductive agent, a first binder and a first organic solvent to obtain a positive electrode slurry; step S2, mixing a negative electrode active material, a second binder, a thickener and a second organic solvent to obtain a negative electrode slurry; step S3, coating the positive electrode slurry on a current collector, and obtaining a positive electrode sheet after drying, rolling and punching, and coating the negative electrode slurry on a current collector, and obtaining a negative electrode sheet after drying, rolling and punching; step S4, stacking the negative electrode sheet, the separator and the positive electrode sheet in sequence to obtain a winding core; step S5, after loading the winding core into an aluminum-plastic packaging shell, injecting an electrolyte into the aluminum-plastic packaging shell for chemical formation to obtain a lithium-ion battery.

[0013] Furthermore, the solid content of the positive electrode slurry is 70-75%; and / or the viscosity of the positive electrode slurry is 4000-6000 cP; and / or the solid content of the negative electrode slurry is 45-50%; and / or the viscosity of the negative electrode slurry is 3000-5000 cP.

[0014] Applying the technical solution of the present application, the polarization of lithium-ion batteries mainly includes electrochemical polarization, ohmic polarization and diffusion polarization. Too large a particle size will increase the distance that lithium ions reach the surface, while too small a particle size may cause the mechanical properties of the material to decrease. Controlling the particle size of the positive electrode active material and the particle size of the negative electrode active material within the above range helps to shorten the lithium ion diffusion path, thereby helping to accelerate the embedding and de-embedding process of lithium ions in the positive electrode active material and the negative electrode active material, and helps to improve the reactivity and contact area of ​​the positive electrode active material and the negative electrode active material, thereby helping to reduce the resistance of lithium ions to the transmission inside the positive electrode active material and the negative electrode active material, and then helping to reduce electrochemical polarization. The high conductivity of the electrolyte means that it has better ion transmission capacity, can more effectively support the rapid charging and discharging process, and reduce the voltage drop caused by the internal resistance of the battery, but too high conductivity means that the ions in the electrolyte move faster, which may lead to the intensification of side reactions. Controlling the conductivity of the electrolyte within the above range helps to increase the mobility of lithium ions while improving the stability of the electrolyte, thereby helping to reduce the ohmic polarization and diffusion polarization of the lithium-ion battery. As a whole, the improvement of a single factor in the lithium-ion battery has limited effect on reducing polarization. The present application simultaneously improves the particle size of the positive electrode active material, the particle size of the negative electrode active material, and the conductivity of the electrolyte, and the synergistic effect between the three helps to significantly reduce the polarization of the lithium-ion battery. DETAILED DESCRIPTION

[0015] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.

[0016] As analyzed in the background technology of the present application, the prior art lithium-ion batteries have the problem of high polarization degree. In order to solve this problem, the present application provides a lithium-ion battery and a preparation method thereof.

[0017] In a typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises a positive electrode active material, and the D50 particle size of the positive electrode active material is 4 to 10 μm; the negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises a negative electrode active material, and the D50 particle size of the negative electrode active material is 10 to 20 μm; and the conductivity of the electrolyte is 10.0 to 12.0 mS / cm.

[0018] The polarization of lithium-ion batteries mainly includes electrochemical polarization, ohmic polarization and diffusion polarization. Too large a particle size will increase the distance that lithium ions reach the surface, while too small a particle size may cause the mechanical properties of the material to deteriorate. Controlling the particle size of the positive electrode active material and the particle size of the negative electrode active material within the above range helps to shorten the lithium ion diffusion path, thereby helping to accelerate the embedding and deintercalation process of lithium ions in the positive electrode active material and the negative electrode active material, and helps to improve the reactivity and contact area of ​​the positive electrode active material and the negative electrode active material, thereby helping to reduce the resistance of lithium ions to the internal transmission of the positive electrode active material and the negative electrode active material, thereby helping to reduce electrochemical polarization. The high conductivity of the electrolyte means that it has better ion transmission capacity, can more effectively support the rapid charging and discharging process, and reduce the voltage drop caused by the internal resistance of the battery, but too high a conductivity means that the ions in the electrolyte move faster, which may lead to the aggravation of side reactions. Controlling the conductivity of the electrolyte within the above range helps to accelerate the movement rate of lithium ions while improving the stability of the electrolyte, thereby helping to reduce the ohmic polarization and diffusion polarization of lithium-ion batteries. As a whole, the improvement of a single factor of lithium-ion batteries has limited effect on reducing polarization. The present application simultaneously improves the particle size of the positive electrode active material, the particle size of the negative electrode active material, and the conductivity of the electrolyte. The synergistic effect between the three helps to significantly reduce the polarization of lithium-ion batteries.

[0019] In one embodiment of the present application, the ratio of the D50 particle size of the positive electrode active material to the D50 particle size of the negative electrode active material is 1:(2-2.5).

[0020] Controlling the ratio of the D50 particle size of the positive electrode active material to the D50 particle size of the negative electrode active material within the above range helps to achieve a good balance in the transfer rate of lithium ions between the positive electrode active material and the negative electrode active material, helps to reduce the polarization phenomenon caused by the mismatch of lithium ion transfer rate, helps to reduce the electrode polarization impedance of the lithium ion battery, and improves the voltage holding ability of the battery under high rate load, thereby helping to release more capacity.

[0021] In one embodiment of the present application, the surface density of the positive electrode active layer is 100-140 g / m 2 ; and / or, the surface density of the negative electrode active layer is 50 to 100 g / m 2 .

[0022] The surface density affects the porosity of the electrode and the permeability of the electrolyte. Controlling the surface density of the positive electrode active layer and the surface density of the negative electrode active layer within the above range helps to keep the electrode porosity at a reasonable level. Too many pores can easily reduce the energy density, and too few pores are not conducive to the penetration of the electrolyte. The appropriate porosity helps the electrolyte to effectively infiltrate the electrode, promote the transmission of lithium ions, and improve the efficiency of the electrochemical reaction.

[0023] In one embodiment of the present application, the thickness of the positive electrode active layer is 70-100 μm; and / or the thickness of the negative electrode active layer is 70-100 μm.

[0024] An overly thick active layer tends to increase the path length of lithium ions from the inside of the electrode material to the surface, thereby increasing electrochemical polarization and reducing the charge and discharge efficiency of the battery. An overly thin active layer may reduce the energy density. Controlling the thickness of the positive electrode active layer and the thickness of the negative electrode active layer within the above range helps to improve the transmission efficiency of lithium ions while maintaining a high energy density of the lithium-ion battery.

[0025] In one embodiment of the present application, the positive electrode active layer further contains a conductive agent and a first binder; in one embodiment of the present application, the mass ratio of the positive electrode active material, the conductive agent and the first binder is 100:(1-3):(1-3).

[0026] The addition of conductive agent helps to improve the conductivity of the positive electrode sheet and improve the transmission efficiency of lithium ions between the positive electrode active material particles. The function of the binder is to firmly adhere the positive electrode active material and the conductive agent to the current collector to form a stable and uniform positive electrode active layer. Too much conductive agent and binder will occupy the space of the positive electrode active material, which is not conducive to improving the energy density of lithium-ion batteries. Controlling the mass ratio of the positive electrode active material, the conductive agent and the first binder within the above range helps to make the positive electrode active layer have a higher energy density while reducing the resistance inside the electrode, thereby reducing electrochemical polarization and improving the charge and discharge performance and cycle stability of the battery at high rates.

[0027] In one embodiment of the present application, the above-mentioned positive electrode active material is selected from any one or more of lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate; and / or, the conductive agent is selected from any one or more of carbon nanotubes, graphene and conductive carbon black; and / or, the first binder is selected from any one or more of polytetrafluoroethylene, carboxylated polyvinylidene fluoride and polyimide; in one embodiment of the present application, the positive electrode active material is lithium cobalt oxide; and / or, the conductive agent is carbon nanotubes; and / or, the first binder is polytetrafluoroethylene.

[0028] Controlling the types of positive electrode active materials, conductive agents and the first binder within the above range helps to enrich the selectivity of the materials. In particular, controlling the positive electrode active material to be lithium cobalt oxide, the conductive agent to be carbon nanotubes and the first binder to be polytetrafluoroethylene helps to optimize the electrochemical performance of the battery and improve the mechanical strength, structural stability and safety of the battery. Specifically, lithium cobalt oxide has a higher operating voltage and a stable crystal structure, which helps to provide a higher energy density. Carbon nanotubes have excellent conductivity and mechanical strength, which helps to enhance the electronic conductive network of the positive electrode active layer, reduce internal resistance, and improve the charge and discharge efficiency of the battery. Polytetrafluoroethylene has good chemical stability and high temperature resistance, which helps to stably bond the active material and the conductive agent under the battery working environment and reduce bonding failure caused by environmental changes.

[0029] In one embodiment of the present application, the negative electrode active layer further contains a second binder and a thickener; in one embodiment of the present application, the mass ratio of the negative electrode active material, the second binder and the thickener is 100:(1-5):(1-5).

[0030] The negative electrode active material is a key part of battery energy storage, and the addition of the second binder and thickener affects the structural stability of the electrode and the distribution of the electrolyte. Controlling the mass ratio of the negative electrode active material, the second binder and the thickener within the above range helps to improve the uniformity of the distribution of the negative electrode active material in the electrode and improve the stability of the electrode structure, thereby helping to increase the capacity of the battery and reduce polarization.

[0031] In one embodiment of the present application, the negative electrode active material is graphite; and / or the second binder is styrene-butadiene latex binder; and / or the thickener is sodium carboxymethyl cellulose.

[0032] Graphite has a high lithium storage density and good cycle stability, and can provide high-capacity lithium storage performance, thereby increasing the energy density of the battery. Styrene-butadiene latex binder can effectively bond active materials and current collectors, improve the mechanical strength and stability of the negative electrode, and reduce the shedding of active materials during the charge and discharge cycle. Sodium carboxymethyl cellulose can adjust the viscosity of the electrolyte, make the electrolyte more evenly distributed in the electrode, and improve the transmission efficiency of lithium ions. The combination of styrene-butadiene latex binder and sodium carboxymethyl cellulose helps to improve the wettability of the electrolyte between electrode materials, promote the uniform transmission of lithium ions, reduce electrochemical polarization and ohmic polarization, and the combination of styrene-butadiene latex binder and sodium carboxymethyl cellulose can form a stable gel structure, which helps to further enhance the binding force of the electrode material and improve the stability and consistency of the electrode.

[0033] In another typical embodiment of the present application, a method for preparing the aforementioned lithium-ion battery is provided, and the preparation method comprises: step S1, mixing a positive electrode active material, a conductive agent, a first binder and a first organic solvent to obtain a positive electrode slurry; step S2, mixing a negative electrode active material, a second binder, a thickener and a second organic solvent to obtain a negative electrode slurry; step S3, coating the positive electrode slurry on a current collector, and obtaining a positive electrode sheet after drying, rolling and punching, and coating the negative electrode slurry on a current collector, and obtaining a negative electrode sheet after drying, rolling and punching; step S4, stacking the negative electrode sheet, the separator and the positive electrode sheet in sequence to obtain a winding core; step S5, after loading the winding core into an aluminum-plastic packaging shell, injecting an electrolyte into the aluminum-plastic packaging shell for chemical formation to obtain a lithium-ion battery.

[0034] The present application can prepare a lithium-ion battery with a lower degree of polarization through conventional lithium-ion battery preparation steps.

[0035] Including but not limited to, the first organic solvent is selected from any one or more of N-methyl-2-pyrrolidone, polyvinylpyrrolidone and triethyl phosphite; the second organic solvent is selected from any one or more of anhydrous ethanol, N-methyl-2-pyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide; the diaphragm is selected from any one or more of polyethylene diaphragm, polypropylene diaphragm and glass fiber diaphragm; the current collector is selected from copper foil and / or aluminum foil.

[0036] In one embodiment of the present application, the solid content of the above-mentioned positive electrode slurry is 70-75%; and / or, the viscosity of the positive electrode slurry is 4000-6000 cP; and / or, the solid content of the negative electrode slurry is 45-50%; and / or, the viscosity of the negative electrode slurry is 3000-5000 cP.

[0037] Controlling the solid content and viscosity of the positive electrode slurry and the solid content and viscosity of the negative electrode slurry within the above range helps to improve the wettability of the active layer and promote the uniform distribution of the electrolyte, thereby helping to optimize the transmission path and speed of lithium ions in the positive and negative electrodes and reduce the ohmic polarization and diffusion polarization of the battery.

[0038] In one embodiment of the present application, the electrolyte comprises a lithium salt, a third organic solvent and an additive. In one embodiment of the present application, the lithium salt is lithium hexafluorophosphate; and / or the third organic solvent is selected from any one or more of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate; and / or the additive is vinyl carbonate.

[0039] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0040] Example 1

[0041] Positive electrode sheet: Lithium cobalt oxide with a D50 particle size of 4 μm, carbon nanotubes and polytetrafluoroethylene were added to N-methyl-2-pyrrolidone in a mass ratio of 100:1:3 and mixed to obtain a positive electrode slurry. The solid content of the positive electrode slurry was 70%, and the viscosity of the positive electrode slurry was 4000 cP. The positive electrode slurry was coated on a copper foil, and a positive electrode sheet was obtained after drying, rolling and punching. The surface density of the positive electrode active layer in the positive electrode sheet was 100 g / m 2 , thickness is 70μm.

[0042] Negative electrode sheet: Graphite with a D50 particle size of 10 μm, styrene-butadiene latex binder and sodium carboxymethyl cellulose were added to N-methyl-2-pyrrolidone in a mass ratio of 100:1:5 and mixed to obtain a negative electrode slurry. The solid content of the negative electrode slurry was 45%, and the viscosity of the negative electrode slurry was 3000 cP. The negative electrode slurry was coated on a copper foil, and a negative electrode sheet was obtained after drying, rolling and punching. The surface density of the negative electrode active layer in the negative electrode sheet was 50 g / m 2 , thickness is 70μm.

[0043] Electrolyte: Ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate are mixed in a volume ratio of 30:50:20 to obtain a mixed organic solvent, and lithium hexafluorophosphate and vinyl carbonate are added to the mixed organic solvent to obtain an electrolyte, wherein the mass proportion of lithium hexafluorophosphate in the electrolyte is 13%, and the conductivity of the electrolyte is 10.0 mS / cm.

[0044] Battery: The negative electrode sheet, polyethylene separator and positive electrode sheet are stacked in sequence to obtain a roll core, and after the roll core is loaded into an aluminum-plastic packaging shell, an electrolyte is injected into the aluminum-plastic packaging shell for formation to obtain a lithium-ion battery.

[0045] Example 2

[0046] The difference from Example 1 is that the D50 particle size of lithium cobalt oxide is 10 μm, and the D50 particle size of graphite is 20 μm, and a lithium ion battery is finally obtained.

[0047] Example 3

[0048] The difference from Example 1 is that the D50 particle size of lithium cobalt oxide is 4 μm, and the D50 particle size of graphite is 10 μm, and a lithium ion battery is finally obtained.

[0049] Example 4

[0050] The difference from Example 1 is that the D50 particle size of lithium cobalt oxide is 10 μm, the D50 particle size of graphite is 10 μm, and a lithium ion battery is finally obtained.

[0051] Example 5

[0052] The difference from Example 1 is that the conductivity of the electrolyte is adjusted to 12.0 mS / cm by adjusting the mass ratio of vinyl carbonate, and finally a lithium ion battery is obtained.

[0053] Example 6

[0054] The difference from Example 1 is that the surface density of the positive electrode active layer is 140 g / m 2 The surface density of the negative electrode active layer is 100g / m 2 , and finally a lithium-ion battery is obtained.

[0055] Example 7

[0056] The difference from Example 1 is that the surface density of the positive electrode active layer is 160 g / m 2 The surface density of the negative electrode active layer is 120g / m 2 , and finally a lithium-ion battery is obtained.

[0057] Example 8

[0058] The difference from Example 1 is that the thickness of the positive electrode active layer is 100 μm, the thickness of the negative electrode active layer is 100 μm, and finally a lithium ion battery is obtained.

[0059] Example 9

[0060] The difference from Example 1 is that the thickness of the positive electrode active layer is 130 μm, and the thickness of the negative electrode active layer is 110 μm, and finally a lithium ion battery is obtained.

[0061] Example 10

[0062] The difference from Example 1 is that the mass ratio of lithium cobalt oxide, carbon nanotubes and polytetrafluoroethylene is 100:3:1, and a lithium ion battery is finally obtained.

[0063] Embodiment 11

[0064] The difference from Example 1 is that the mass ratio of lithium cobalt oxide, carbon nanotubes and polytetrafluoroethylene is 100:4:1, and a lithium ion battery is finally obtained.

[0065] Example 12

[0066] The difference from Example 1 is that the mass ratio of graphite, styrene-butadiene latex binder and sodium carboxymethyl cellulose is 100:5:1, and a lithium ion battery is finally obtained.

[0067] Example 13

[0068] The difference from Example 1 is that the mass ratio of graphite, styrene-butadiene latex binder and sodium carboxymethyl cellulose is 100:6:1, and a lithium ion battery is finally obtained.

[0069] Embodiment 14

[0070] The difference from Example 1 is that the solid content of the positive electrode slurry is 75%, the viscosity of the positive electrode slurry is 6000 cP, the solid content of the negative electrode slurry is 50%, the viscosity of the negative electrode slurry is 5000 cP, and finally a lithium ion battery is obtained.

[0071] Embodiment 15

[0072] The difference from Example 1 is that the solid content of the positive electrode slurry is 80%, the viscosity of the positive electrode slurry is 8000 cP, the solid content of the negative electrode slurry is 55%, the viscosity of the negative electrode slurry is 6000 cP, and finally a lithium ion battery is obtained.

[0073] Comparative Example 1

[0074] The difference from Example 1 is that the D50 particle size of lithium cobalt oxide is 15 μm, and the D50 particle size of graphite is 5 μm, and a lithium ion battery is finally obtained.

[0075] Comparative Example 2

[0076] The difference from Example 1 is that the D50 particle size of graphite is 5 μm, the conductivity of the electrolyte is 15.0 mS / cm, and a lithium ion battery is finally obtained.

[0077] Comparative Example 3

[0078] The difference from Example 1 is that the D50 particle size of lithium cobalt oxide is 15 μm, the conductivity of the electrolyte is 15.0 mS / cm, and a lithium ion battery is finally obtained.

[0079] The lithium ion batteries prepared in the above embodiments and comparative examples were first discharged at 1C to 3.0V at 25°C, and then charged at 1C constant current and constant voltage to 4.2V with a cut-off current of 0.02C. They were then discharged at 11.4C to test the initial voltage value. At the same time, the initial discharge capacity at 11.4C was recorded. The battery was charged at 1C and discharged at 4A for 300 cycles. The capacity retention rate after 300 cycles was tested. The test results are shown in Table 1.

[0080] Table 1

[0081]

[0082]

[0083] As can be seen from Table 1, the initial voltage of the comparative example at high rate is lower than that of the present invention, indicating that the battery polarization of the present invention is lower. The cycle capacity retention rate of the embodiment is similar to that of the comparative example, indicating that the battery cycle stability of the present invention is not affected.

[0084] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0085] The polarization of lithium-ion batteries mainly includes electrochemical polarization, ohmic polarization and diffusion polarization. Too large a particle size will increase the distance that lithium ions reach the surface, while too small a particle size may cause the mechanical properties of the material to deteriorate. Controlling the particle size of the positive electrode active material and the particle size of the negative electrode active material within the above range helps to shorten the lithium ion diffusion path, thereby helping to accelerate the embedding and deintercalation process of lithium ions in the positive electrode active material and the negative electrode active material, and helps to improve the reactivity and contact area of ​​the positive electrode active material and the negative electrode active material, thereby helping to reduce the resistance of lithium ions to the internal transmission of the positive electrode active material and the negative electrode active material, thereby helping to reduce electrochemical polarization. The high conductivity of the electrolyte means that it has better ion transmission capacity, can more effectively support the rapid charging and discharging process, and reduce the voltage drop caused by the internal resistance of the battery, but too high a conductivity means that the ions in the electrolyte move faster, which may lead to the aggravation of side reactions. Controlling the conductivity of the electrolyte within the above range helps to accelerate the movement rate of lithium ions while improving the stability of the electrolyte, thereby helping to reduce the ohmic polarization and diffusion polarization of lithium-ion batteries. As a whole, the improvement of a single factor of lithium-ion batteries has limited effect on reducing polarization. The present application simultaneously improves the particle size of the positive electrode active material, the particle size of the negative electrode active material, and the conductivity of the electrolyte. The synergistic effect between the three helps to significantly reduce the polarization of lithium-ion batteries.

[0086] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode sheet includes a positive electrode active layer, the positive electrode active layer contains positive electrode active materials, and the D50 particle size of the positive electrode active materials is 4 to 10 μm; the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer contains negative electrode active materials, and the D50 particle size of the negative electrode active materials is 10 to 20 μm; the conductivity of the electrolyte is 10.0 to 12.0 mS / cm.

2. The lithium-ion battery according to claim 1, characterized in that The ratio of the D50 particle size of the positive electrode active material to the D50 particle size of the negative electrode active material is 1:(2-2.5).

3. The lithium ion battery according to claim 1 or 2, characterized in that: The surface density of the positive electrode active layer is 100 to 140 g / m 2 ; and / or, the surface density of the negative electrode active layer is 50 to 100 g / m 2 .

4. The lithium ion battery according to any one of claims 1 to 3, characterized in that The thickness of the positive electrode active layer is 70 to 100 μm; and / or the thickness of the negative electrode active layer is 70 to 100 μm.

5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The positive electrode active layer further contains a conductive agent and a first binder; preferably, the mass ratio of the positive electrode active material, the conductive agent and the first binder is 100:(1-3):(1-3).

6. The lithium-ion battery according to claim 5, characterized in that: The positive electrode active material is selected from any one or more of lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate; and / or, the conductive agent is selected from any one or more of carbon nanotubes, graphene and conductive carbon black; and / or, the first binder is selected from any one or more of polytetrafluoroethylene, carboxylated polyvinylidene fluoride and polyimide; Preferably, the positive electrode active material is lithium cobalt oxide; and / or the conductive agent is carbon nanotubes; and / or the first binder is polytetrafluoroethylene.

7. The lithium ion battery according to any one of claims 1 to 6, characterized in that The negative electrode active layer further contains a second binder and a thickener; preferably, the mass ratio of the negative electrode active material, the second binder and the thickener is 100:(1-5):(1-5).

8. The lithium-ion battery according to claim 7, characterized in that: The negative electrode active material is graphite; and / or the second binder is styrene-butadiene latex binder; and / or the thickener is sodium carboxymethyl cellulose.

9. A method for preparing a lithium ion battery according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Step S1, mixing a positive electrode active material, a conductive agent, a first binder and a first organic solvent to obtain a positive electrode slurry; Step S2, mixing the negative electrode active material, the second binder, the thickener and the second organic solvent to obtain a negative electrode slurry; Step S3, coating the positive electrode slurry on the current collector, drying, rolling and punching to obtain a positive electrode sheet, coating the negative electrode slurry on the current collector, drying, rolling and punching to obtain a negative electrode sheet; Step S4, stacking the negative electrode sheet, the separator and the positive electrode sheet in sequence to obtain a winding core; Step S5, after the winding core is loaded into the aluminum-plastic packaging shell, an electrolyte is injected into the aluminum-plastic packaging shell for chemical formation to obtain the lithium-ion battery.

10. The preparation method according to claim 9, characterized in that: The solid content of the positive electrode slurry is 70-75%; and / or, the viscosity of the positive electrode slurry is 4000-6000 cP; and / or, the solid content of the negative electrode slurry is 45-50%; and / or, the viscosity of the negative electrode slurry is 3000-5000 cP.

Citation Information

Patent Citations

  • Lithium ion battery

    CN104779413A

  • Lithium ion battery capable of being charged quickly and preparation method of lithium ion battery

    CN106356526A

  • Ultrahigh-power, wide-temperature-range and high-safety lithium ion battery and preparation method thereof

    CN117936918A

  • Battery monomer, preparation method thereof and lithium ion battery

    CN119208700A

  • Lithium secondary battery

    US20210066744A1

Cited By

  • Battery and electric device

    CN121885764A

  • Lithium-ion battery and preparation method therefor

    WO2026144201A1